Individualized nutritional care for a pediatric patient: case report - Morgado Lamonica, Thaís; Sílvia Frangella, Vera; Pessina, Elen (O Mundo da Saúde, 2008)
This nutritional care program was carried through with a pediatric patient having Chronic Renal Insufficiency, Hemolytic-Uremic Syndrome, and Arterial Hypertension, chosen due to the necessity of favoring her clinical condition, due to the high rates of morbiditymortality in renal children. The aim of this work is to promote growth, development, and survival with life quality. This clinical-case type experimental research had as subject a 5-year boy years. For doing this, we examined data from the hospital record such as pharmacotherapy and results of the requested exams. An Alimentary Inquiry was applied, and we evaluated and calculated the Alimentary Record. Nutritional diagnosis was defined by the evaluation of biochemical and anthropometric parameters. After dietary planning, nutritional and clinical necessities of the patient were considered to promote adaptations to the hospital diet. The analysis of the domiciliary record suggests that inadequate alimentary consumption favored the clinical diagnosis. Nutritional evaluation identified a risk of malnutrition regarding protein intake. Due to the patient’s inapetence, the offered oral diet was modified, promoting a better acceptance of food without, however, reaching the ideal consumption of nutrients. The persistent inadequateness of ingestion favors weight loss and a higher nutritional depletion and reduces the patient’s survival. The study shows this way the necessity of a continuous nutritional assistance, suggesting that oral nutritional supplements be offered.